2019
DOI: 10.1039/c9sm00890j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced diffusion and magnetophoresis of paramagnetic colloidal particles in rotating magnetic fields

Abstract: Dispersions of paramagnetic colloids can be manipulated with external magnetic fields to assemble structures via dipolar assembly and control transport via magnetophoresis. For fields held steady in time, the dispersion structure and dynamic properties are coupled. This coupling can be problematic when designing processes involving field-induced forces, as particle aggregation competes against and hinders particle transport. Time-varying fields drive dispersions out-of-equilibrium, allowing the structure and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Extensive research has shown that the magnetic ζ potential on the surface of magnetic powder is negatively charged ( Amiralian et al 2020; Scardigli et al 2021), the positive ions generated by the aqueous solution of coagulant gather around the negatively charged colloidal particles and magnetic powder under the effect of electric neutralization. As the static electromagnetic force disappears, the colloidal particles and magnetic powder particles are aggregated under the effect of van der Waals force, and then the ocs are further agglomerated and enlarged by the adsorption bridging effect of occulant, which nally makes the pollutants and water departed from wastewater (Lin et al 2021; Hamoud, Finqueneisel and Azambre 2017; Sherman et al 2019).…”
Section: )mentioning
confidence: 99%
“…Extensive research has shown that the magnetic ζ potential on the surface of magnetic powder is negatively charged ( Amiralian et al 2020; Scardigli et al 2021), the positive ions generated by the aqueous solution of coagulant gather around the negatively charged colloidal particles and magnetic powder under the effect of electric neutralization. As the static electromagnetic force disappears, the colloidal particles and magnetic powder particles are aggregated under the effect of van der Waals force, and then the ocs are further agglomerated and enlarged by the adsorption bridging effect of occulant, which nally makes the pollutants and water departed from wastewater (Lin et al 2021; Hamoud, Finqueneisel and Azambre 2017; Sherman et al 2019).…”
Section: )mentioning
confidence: 99%
“…[1][2][3][4][5][6] A subset of active matter systems are synthetic microswimmers, which have in the recent years attracted large attention due to their potential in mimicking biological microorganisms, 7 in practical applications in fields such as microfluidics or microsurgery, 4,8 or in the development of new bio-mimetic materials. 6 Artificial microswimmers with a locomotion based on phoretic effects behave as passive colloids unless activated via thermal, [9][10][11][12][13] electric, [14][15][16][17][18] chemical, 19,20 or magnetic [21][22][23] gradients. Thermally activated phoretic microswimmers, or thermophoretic swimmers, are colloids whose surfaces are composed of or simply coated by materials with different absorption coefficients, such that local temperature gradients are created around the colloid by environmental heating.…”
Section: Introductionmentioning
confidence: 99%
“…Stokes flow, also known as creeping flow or viscous flow, is a model of fluid flow in which inertial forces are assumed to be negligible in comparison to viscous forces (i.e., the Reynolds number is very small). This is often a valid assumption for phenomena involving suspension flows on the micro-and nanoscales (often in combination with Brownian motion), such as swimming microorganisms [1], cell dynamics [2], microfluidic devices [3], gels [4,5], dynamics of nanoparticles and nanofibrils [6,7,8,9], electrolytes [10], and antibodies [11]. For Stokes flow, the Navier-Stokes equations reduce to the Stokes equations, which for an incompressible Newtonian fluid are given by −∇p(x) + µ∇ 2 u(x) + g(x) = 0,…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the inclusion of Brownian motion, [27] proposed the Positively Split Ewald (PSE) method for the Rotne-Prager-Yamakawa (RPY) tensor of Stokesian dynamics, thus ensuring that both the short-range and long-range parts are symmetric positive definite. The PSE method has found much use in Brownian dynamics [28,29,30,4,7,5,11,31,2,8,9].…”
Section: Introductionmentioning
confidence: 99%